Narcissistic Personality Disorder through psycholinguistic analysis and neuroscientific correlates - Elleuch, Dalia (Frontiers in Behavioral Neuroscience, 2024)
Narcissistic Personality Disorder (NPD) is characterized by inflated self-importance, heightened sensitivity to criticism, a lack of empathy, and a preoccupation with appearance over substance. It includes features such as arrogance, grandiosity, a constant need for admiration, a tendency to exploit others, and a persistent demand for special treatment due to excessive entitlement. This interdisciplinary study delves into NPD by synthesizing psycholinguistic analysis and neuroscientific correlates. The cognitive and emotional dimensions of NPD reveal linguistic patterns, such as grandiosity, entitlement, and manipulative communication. Neuroscientific investigations highlight structural brain differences and alterations in functional connectivity, the neural underpinnings of social cognition deficits observed in individuals with NPD. Genetic predispositions and neurotransmitter imbalances add further complexity to the understanding of NPD. The necessity for linguistic intervention in diagnosing and treating NPD is underscored by this interdisciplinary study that provides a multidimensional understanding of NPD's cognitive, emotional, and neural dimensions. It paves the way for future practical, theoretical, and pedagogical approaches to address the complexities of this personality disorder.